Long lives, short indications - Ku, Grace H.; Billett, Henny H. (Thrombosis and Haemostasis, 2005)
Vena cava filters have been in use for decades to prevent pulmonary embolization from deep venous thrombosis. These filters have been shown to be effective, with fairly low rates of filter migration, fracture and thrombosis. However considering that filters remain in situ for the life of the patient and that studies do not show increased longevity in patients with filters, any complications from filters are significant concerns. In addition, often patients require filters for only temporary indications, e.g. contraindication for anticoagulation because of impending procedures, or for only a transient risk period, as in trauma or pregnant patients. In these cases, removable filters may be more appealing. This review will examine the different types of removable filters and the indications in which removable filters may have an advantage over permanent filters.
Keywords: Temporary; removable; retrievable; vena cava filter